Effect of saline stress on growth and biochemical indices of chrysanthemum (Chrysanthemum morifolium) germplasm - VANLALRUATI, VANLALRUATI; ANAND, PRATIVA; KUMAR, GUNJEET; TIWARI, A K (The Indian Journal of Agricultural Sciences, 2019)
Chrysanthemum (Chrysanthemum morifolium Ramat.) is one of the most popular cut flowers in the world and occupies important position in the world flower industry. An experiment was conducted to study the effect of saline stress on growth and biochemical indices on 10 chrysanthemum germplasm. It was determined by performance comparisons against control tests (without NaCl treatment) which acts as an indicator. Germplasm selected for the experiment were Garden Beauty, Shanti, Red Stone, Basanti, Yellow Reflex, Arka Ravikiran, Anmol, Mother Teresa, Sweta Singar and Jaya. Salt stress had significant effects on plant growth, assimilator pigment content and proline concentration. With application of 150 mM NaCl, there is reduction of shoot growth, root growth, leaf area, leaf number, shoot dry weight and chlorophyll content, whereas level of proline increased with increase salinity. Shoot elongation was less sensitive to salinity than root growth, with significant reductions in root growth at high salinity levels (150 mM). The genotype- Garden Beauty (5.03%) recorded minimum shoot length reduction, whereas minimum shoot dry weight reduction was observed in Anmol (23.97%) with increasing salinity. The genotype Basanti (2.35%) recorded minimum reduction in root growth. Minimum reduction in photosynthetic pigments was observed in Mother Teresa (51.55%) and high accumulation of proline content was recorded in Sweta Singar (162.50%). The genotypes Mother Teresa, Anmol, Basanti and Sweta Singar were found to be tolerant due to enhanced photosynthetic pigments, proline concentration and better shoot and root growth with higher salinity.